PATIENT CARE AND CONTROL IN RESPIRATORY DISEASES (Multidisciplinary Journal of Science and Technology, 2025)
This article provides comprehensive information on the epidemiology, pathophysiology, clinical manifestations, modern care methods and monitoring measures of diseases of the respiratory system, in particular chronic obstructive pulmonary disease (COPD), bronchial asthma, pneumonia, acute respiratory infections and pulmonary fibrosis. Based on a scientific approach, clear and practical recommendations are given on the prevention of diseases, reducing complications, improving the functional state of patients, accelerating the recovery process and improving the quality of life. Particular attention is paid to environmental factors (salinity and dust in the Aral Sea region), occupational hazards (cotton dust and chemicals), socio-economic problems and limitations of the healthcare system (lack of resources and qualified personnel) that affect the spread of diseases in the conditions of Uzbekistan. The article is based on international clinical guidelines (AARP, ATS, ERS), recent scientific research and local healthcare experience of Uzbekistan. The application of modern technologies, such as remote patient monitoring (RPM) and telemedicine, as well as proposals for eliminating problems in the healthcare system are presented. The article is aimed at developing an integrated approach to care, strengthening preventive measures and improving population health.